Legal Protection of Consumers in E-commerce Through Social Media in Indonesia in the Industrial Era 4.0 - Aris Surya Muzakki; Suraji Suraji (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia has a large population of internet users, with more than 175 million active internet users in 2021 to 2024. This provides a strong foundation for the development of social media in the country. The increasing use of smartphones in Indonesia also has an impact on the development of social media and online buying and selling (e-commerce). The Indonesian government has issued laws and regulations regarding the use of social media with a focus on online buying and selling and handling infringing content. This research uses normative juridical methods. One of the challenges in buying and selling transactions via social media is security and trust. Because these transactions are often conducted between individuals who do not know each other, it is important to be careful and verify the seller or buyer before making a transaction. Consumer law in Indonesia is regulated by Law Number 8 of 1999 concerning Consumer Protection (Consumer Law). This Consumer Law provides a legal basis and legal protection for consumers in carrying out buying and selling transactions, both conventionally and via social media.